SOSIALISASI STRATEGI PEMASARAN DAN PENGEMASAN PRODUK PADA UKM PEYEK DI DESA FIRDAUS - Ghalih Anwar; Adrial Falahi (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
In today's increasingly competitive business world, entrepreneurs need to employ integrated marketing strategies designed to improve consumer purchasing decisions. In order to survive, develop and compete, companies must be able to maintain a high level of customer satisfaction. There are many ways to keep customers satisfied, one of them is by always improving the quality of the products sold and the correct and attractive product packaging. Socializing, involving and forming village communities in marketing and packaging, expanding marketing reach, and increasing the selling price of products with unique packaging. In the process of perfecting the marketing strategy and product packaging, through direct interviews with the community, then socialization of residents with small and medium businesses. The results of the implementation of the program can be concluded that the unique online marketing and packaging is very helpful for the marketing and packaging of buckwheat products. In addition, online marketing can help introduce products and the potential of small and medium businesses (home industry) to be marketed to consumers